JNE’s Cross-Media Communication Strategy to Strengthen the “Connecting Happiness” Brand Narrative - Siska Ramadhani; Aryo Subarkah Eddyono (Jurnal Indonesia Sosial Sains, 2026)
This study examines JNE's cross-media communication strategy in delivering the "Connecting Happiness" brand narrative across digital and conventional platforms. The research is motivated by increasing competition in Indonesia's logistics industry and the need for logistics companies to build emotional customer connections beyond transactional relationships. The purpose is to analyze how JNE integrates the brand narrative across multiple channels, adapts messages to each platform's unique characteristics, and maintains consistency in communication practices. Employing a qualitative case study method, data were collected through in-depth interviews with JNE's Media Communication Head and content observation across Instagram, TikTok, YouTube, X, the official website, and internal publications. The analysis focused on identifying patterns of narrative integration, message adaptation, and consistency of the "Connecting Happiness" theme across channels. The findings reveal that JNE applies transmedia storytelling practices, where the narrative is developed into complementary stories across each platform rather than repeating identical content. Social media serves for emotional engagement, the website for credibility, conventional media for legitimacy, and offline activities for community interaction. The "Joni" mascot reinforces the brand's human-centric identity across all channels. The results demonstrate that JNE has successfully positioned itself not merely as a logistics provider but as a brand carrying emotional value in people's lives. This research contributes theoretical insights to digital communication literature on cross-media practices in logistics, while offering practical guidance for building emotional brand connections through integrated media strategies. Future research is recommended to explore transmedia storytelling's long-term impact on customer loyalty and brand equity.